STUDY OF SERUM ELECTROLYTES AND ARRHYTHMIAS IN FIRST 24 HOURS OF ACUTE MYOCARDIAL INFARCTION - v s, Irshad; sarode, Rajesh; kumar, Sunil; acharya, Sourya (International Journal of Psychosocial Rehabilitation, 2020)
acute myocardial infarction is a major cause of death and disability in both developed and developing countries. To correlate various electrolytes(na,k,ca,mg) abnormalities with arrythmias in acute myocardial infarction during the first 24 hours of admission.To correlate types of arrythmias in first 24 hours of acute myocardial infarction with relation to site of infarction. Patient fulfilling diagnostic criteria of acute myocardial infarction Evaluation of serum electrolytes like serum k,Mg,Na,Ca at the time of admission.Recording of ECG at the time admission and subsequently at 6hour interval and as when needed I expect from the following study that there will be presence of co-relation of serum electrolytes imbalance and arrhythmias in 1st 24 hours of myocardial infarctionConclusions will be drawn when expected outcomes will be received.